Bridges and watersheds : a narrative analysis of water management in England, Wales and the Netherlands - Dicke, Willemijn (Amsterdam : Aksant, 2001)
This study considers water management as a universal issue. It analyses contemporary thinking on water management in England and Wales and the Netherlands and asks how these countries respond to modern challenges.
boek